Considerations for enhanced mesenchymal stromal/stem cell myogenic commitment in vitro - Simone Grobbelaar; Anne E. Mercier; Iman van denBout; Chrisna Durandt; Michael S. Pepper (Wiley, 2024)
Abstract The generation of tissue from stem cells is an alluring concept as it holds a number of potential applications in clinical therapeutics and regenerative medicine. Mesenchymal stromal/stem cells (MSCs) can be isolated from a number of different somatic sources, and have the capacity to differentiate into adipogenic, osteogenic, chondrogenic, and myogenic lineages. Although the first three have been extensively investigated, there remains a paucity of literature on the latter. This review looks at the various strategies available in vitro to enhance harvested MSC commitment and differentiation into the myogenic pathway. These include chemical inducers, myogenic‐enhancing cell culture substrates, and mechanical and dynamic culturing conditions. Drawing on information from embryonic and postnatal myogenesis from somites, satellite, and myogenic progenitor cells, the mechanisms behind the chemical and mechanical induction strategies can be studied, and the sequential gene and signaling cascades can be used to monitor the progression of myogenic differentiation in the laboratory. Increased understanding of the stimuli and signaling mechanisms in the initial stages of MSC myogenic commitment will provide tools with which we can enhance their differentiation efficacy and advance the process to clinical translation.